Requirements prioritization with respect to Geographically Distributed Stakeholders - Ahmad, A.; Shahzad, A.; Padmanabhuni, V. K.; Mansoor, A.; Joseph, S.; Arshad, Z. (2011 IEEE International Conference on Computer Science and Automation Engineering, 2011)
Requirements selection for software releases can play a vital role in the success of software product. This selection of requirements is done by different requirements prioritization techniques. This paper discusses limitations of these Requirements Prioritization Techniques (100 Method and Binary Search Tree) with respect to Geographical Distribution of Stakeholders. We conducted two experiments, in this paper, in order to analyze the variations among the results of these Requirements Prioritization Techniques. This paper also discusses attributes that can affect the requirements prioritization when dealing with Geographically Distributed Stakeholders. We conducted first experiment with 100 Dollar method and Binary Search Tree technique and second experiment has been conducted with modified 100 Dollar method and Binary search tree technique. Results of these experiments have been discussed in this paper. This paper provides a framework that can be used to identify those requirements that can play an important role in a product success during distributed development.